ILRI research on antimicrobial use and resistance in smallholder livestock system - Unger, Fred; Sinh Dang-Xuan; Hung Nguyen-Viet; Muloi, Dishon; Moodley, Arshnee (International Livestock Research Institute, 2024)
An overview of the research focus of the CGIAR Antimicrobial Resistance Hub and antimicrobial resistance research in Vietnam.